Synergy of the Combination of Titanate Nanotubes with Titania Nanoparticles for the Photocatalytic Hydrogen Generation from Water-Methanol Mixture Using Simulated Sunlight - Marco Serra; Hermenegildo Garcia (International Journal of Photoenergy)
Alkali digestion of titanium nanoparticles leads, after neutralization, to the formation of titanate nanotubes with long aspect ratio. One salient change in the formation of titanate nanotubes is the observation of an extended visible absorption band up to 550 nm, responsible for their brown colour. Combination of titanate nanotubes with commercial titanium dioxide nanoparticles, either Evonik P25 or Millennium PC500, results in an enhanced photocatalytic activity for hydrogen generation from water-methanol mixtures. This synergy between the two titanium semiconductors has an optimum for a certain proportion of the two components and is observed in both the absence and the presence of platinum or gold nanoparticles. The best efficiency under simulated sunlight irradiation was for a combination of 12 wt.% titanate nanotubes containing 0.32 wt.% platinum in 88 wt.% Millennium PC500, where a two-time increase in the hydrogen generation is observed versus the activity of Millennium PC500 containing platinum. This synergy is proposed to derive from the interfacial electron transfer from titanate nanotubes undergoing photoexcitation at wavelengths in which Millennium PC500 does not absorb this form of titania nanoparticles. Our results illustrate how the combination of several titanium semiconductors can result in an enhancement efficiency with respect to their individual components.